Effects of vessel traffic and underwater noise on the movement, behaviour and vocalisations of bottlenose dolphins in an urbanised estuary - Marley, S.; Salgado Kent, Chandra; Erbe, Christine; Parnum, Iain (Nature Publishing Group, 2017)
© 2017 The Author(s). Abstarct: The potential disturbance of dolphins from tourism boats has been widely discussed in the literature, in terms of both physical vessel presence and associated underwater noise. However, less attention has been paid to the potential impact of non-tourism vessels, despite these being much more widespread and occurring in greater numbers throughout coastal dolphin habitats. The Indo-Pacific bottlenose dolphin (T. aduncus) community using the Fremantle Inner Harbour, Western Australia, is exposed to high levels of vessel traffic. To investigate whether behavioural responses could be occurring, a non-invasive combination of visual and acoustic monitoring was conducted using a theodolite and an autonomous acoustic logger. Dolphins significantly increased their average movement speeds in high vessel densities, but only for some activity states. Behavioural budgets also changed in the presence of vessels, with animals spending greater time travelling and less time resting or socialising. Finally, multiple whistle characteristics varied with rising levels of broadband noise, and other contextual variables. Despite being acoustically specialised for higher frequencies, dolphins had the strongest acoustic variation during low-frequency noise. This study highlights the complexity of disturbance responses in this species, confirming the need for consideration of both surface and acoustic behaviour alongside appropriate contextual data.